Systemic LPS-induced neuroinflammation increases the susceptibility for proteasome inhibition-induced degeneration of the nigrostriatal pathway. (November 2019) - Deneyer, Lauren; Albertini, Giulia; Bentea, Eduard; Massie, Ann
Abstract: Introduction: Besides proteasome dysfunction, neuroinflammation is a common feature in the pathogenesis of Parkinson's disease (PD). Accordingly, peripheral inflammation has been shown to increase the susceptibility of the brain for nigrostriatal degeneration by inducing activation of glial cells and release of pro-inflammatory cytokines in the brain. Given that current animal models of PD fail to recapitulate the pathophysiology occurring in idiopathic PD, the aim of this study was to combine two pathogenic mechanisms (i.e. neuroinflammation and proteasome inhibition) to create a dual-hit mouse model of PD. Methods: We repeatedly injected mice with a low dose of LPS (250 μg/kg/day i. p. for four days) to induce neuroinflammation, followed by a unilateral intranigral injection of lactacystin (LAC; 3 μg). Seven days later, mice were evaluated behaviorally to assess locomotion, anxiety- and depressive-like behavior. Nigrostriatal degeneration was analyzed by measuring striatal dopamine loss as well as loss of nigral dopaminergic neurons. Neuroinflammation was confirmed by quantifying microglial cells in the substantia nigra (SN) and cytokine expression in the striatum. Results: Repeated systemic LPS injections increase the number of microglial cells in the SN and induce a mixed profile of pro- and anti-inflammatory cytokines in the striatum without affecting the integrity of the nigrostriatal pathway. Systemic LPS-induced neuroinflammation, however, increases the susceptibility of the nigrostriatal pathway for LAC-induced degeneration. Conclusion: Recapitulating two relevant etiopathogenic mechanisms of PD - neuroinflammation and proteasome inhibition-, we propose this dual-hit model as a relevant mouse model for PD that could be used to investigate potential therapeutic targets. Highlights: Repeated systemic low-dose LPS injections induce transient sickness behavior. Systemic low-dose LPS injections induce nigrostriatal inflammation. Low-dose systemic LPS injections do not affect nigrostriatal pathway integrity. Prior systemic LPS treatment enhances proteasome inhibition-induced neurodegeneration.